Penerapan Discovery Learning Menggunakan Microsoft Office 365 untuk Meningkatkan Hasil Belajar Kognitif Siswa - Sholihah, Isnaini Maratus; Wahyuni, Tri; Murtiyasa, Budi (Lembaga Yasin AlSys, 2023)
This study aims to determine the increase in cognitive learning outcomes in science subjects of class VIIA students at SMP Batik Surakarta in the 2020/2021 academic year through the application of the online Discovery Learning model.This research is a Classroom Action Research with the research subjects of class VIIA students in the 2020/2021 academic year totaling 29 students. The data collection technique used a cognitive learning outcome test instrument. The research was conducted in 3 cycles. The analysis technique uses a comparison of learning outcomes. The results of classroom action research carried out through three cycles showed that the application of the discovery learning model could significantly improve students' cognitive learning outcomes by 93.5% of students could achieve completeness of science cognitive learning outcomes in energy material in life systems, this was also accompanied by an increase in average. -a grade learning outcomes. As much as 6.5% of the students were still incomplete due to network constraints and the inactivity of students in following learning in accordance with the provisions.